2016
DOI: 10.1177/1087054716658123
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Associated Parental Factors Among Children With ADHD: A Comparative Study

Abstract: The study's findings provide strong evidence that the maltreatment of children with ADHD is more associated with parental factors than with the symptoms of ADHD in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…Unexpectedly, physical/psychological abuse did not have an indirect effect on suicidal ideation, nor did it increase the risk of self-harm via aggressive behavior. Parents who engage in physical and psychological abuse are characterized by high levels of impulsivity [44] and aggression [43]. Predispositions to these traits may be transmitted from parents to children and accentuated by the children's exposure to experiences of early physical/psychological abuse, such that these traits, in the form of problems with attention and impulsivity, could heighten their risk for self-harm later on.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, physical/psychological abuse did not have an indirect effect on suicidal ideation, nor did it increase the risk of self-harm via aggressive behavior. Parents who engage in physical and psychological abuse are characterized by high levels of impulsivity [44] and aggression [43]. Predispositions to these traits may be transmitted from parents to children and accentuated by the children's exposure to experiences of early physical/psychological abuse, such that these traits, in the form of problems with attention and impulsivity, could heighten their risk for self-harm later on.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children and adolescents with ADHD reported higher stress related to their parenting role than parents of children without ADHD (Daly et al, 2007); they use more physical punishment (Alizadeh, Applequist, & Coolidge, 2007) which could explain the association between maltreatment and ADHD. Many authors concluded that children with ADHD are frequently exposed to acts of maltreatment even after controlling all confounding variables (Gul & Gurkan, 2016; Alizadeh, Applequist & Coolidge, 2007; Ouyang, Fang, Mercy, Perou, & Grosse, 2008); 40% of neglect, 30% of physical abuse, and 5% of sexual abuse were found among children with ADHD (Ouyang et al, 2008). A maltreatment rate of 70% was observed in adolescents with ADHD diagnosed and treated since childhood (Sanctis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, there is no reason why neurodevelopmental problems such as ASD and traumaand stressor-related problems such as RAD and DSED could not occur together: A child with heritable ASD could experience maltreatment in the same way as a child without and, in addition, children with inherent deficits in social communication or other symptoms of neurodevelopmental problems may be more at risk of being maltreated if in a vulnerable family (Gul & Gurkan, 2018;Sullivan & Knutson, 2000).We have already shown, in clinic-based research, that ASD and RAD/ DSED can occur together in maltreated children (Kocovska et al, 2012), but the prevalence of cooccurring ASD and RAD/DSED in the population is unknown. Co-occurrence of RAD/DSED and ASD might place children at particularly high risk of current and future physical and mental illness, as has been found when multi-morbidity occurs in adults (Barnett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%